1971
DOI: 10.1002/bjs.1800580611
|View full text |Cite
|
Sign up to set email alerts
|

Topical noxythiolin antisepsis. Report of a controlled trial

Abstract: Noxythiolin powder, 600 mg., deposited in the layers of the abdominal wall of right iliac fossa musclesplitting incisions after appendicectomy seemed to be without serious side‐effects. However, no benefit was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1972
1972
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…WOUND infection has been reported to occur in up to 30 per cent of all patients after appendicectomy (Bird et al, 1971), and the incidence may be as high as 63 per cent in perforated appendicitis (Leigh et al, 1974).…”
Section: Zn Cases With a Gangrenous Or Perforated Appendix The Infectmentioning
confidence: 99%
“…WOUND infection has been reported to occur in up to 30 per cent of all patients after appendicectomy (Bird et al, 1971), and the incidence may be as high as 63 per cent in perforated appendicitis (Leigh et al, 1974).…”
Section: Zn Cases With a Gangrenous Or Perforated Appendix The Infectmentioning
confidence: 99%
“…trials [11,[22][23][24][25][26][27][28] is shown in Table 1. There tends to be little difference between infection rates after removal of a normal or an uncomplicated acutely inflamed appendix among these studies.…”
Section: Incidencementioning
confidence: 99%